Job Quality and Employment of Older People in Europe - Rudolf Winter-Ebmer; Mario Schnalzenberger; Nicole Schneeweis; Martina Zweimüller (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2011)
We study the relationship between job quality and retirement using panel data for European countries (SHARE). While previous studies looked at the impact of bad working conditions on retirement intentions, we can use the panel dimension to study actual retirement as well as other pathways out of a job. As indicators for job quality we use three different approaches: overall job satisfaction, over- and undereducation for a particular job as well as effort-reward imbalance which measures the imbalance between a worker's effort and the rewards he or she receives in turn.
Keywords: J14; J18; J26; J28; 330; retirement; job quality; job satisfaction; educational mismatch; effort-reward imbalance; SHARE